In situ synthesis and optical limiting response of poly(N-vinylcarbazole) functionalized single-walled carbon nanotubes - BLAU, WERNER (Institute of Physics, 2010)
A new poly(N-vinylcarbazole)-covalently grafted single-wall carbon nanotube (SWNT?PVK) hybrid material was synthesized by an in situ anionic polymerization reaction of N-vinylcarbazole and the negatively charged SWNTs. Incorporation of the PVK moieties onto the SWNTs' surface considerably improves the solubility and processability of SWNTs. At the same level of linear transmission, the SWNT?PVK dispersions show better optical limiting performance than the pristine SWNT dispersions, which shows this material to be a suitable candidate for viable optical limiting devices. Micro-plasma and/or micro-bubble induced nonlinear scattering is considered as the main mechanism for optical limiting.
PUBLISHED
Keywords: Physical chemistry; Polymer science